Geldpolitik und Staatsverschuldung - welche Rolle spielt die Unabhängigkeit der Notenbank? - Ralph Solveen (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
– Two theoretical modeis are developed. Both describe the connection between public debt and inflation. In the first one, monetary policy inflates the economy to rcduce the bürden of existing debt. In the second one, the causality runs directly from the level of public debt to inflation via a change in the velocity of money. In both modeis the independence of the central bank influences the level of public debt, the elasticity of inflation with respect to the amount of public debt and the reaction of monetary policy to rising debt. In the next part of the paper it is tested for these theses. The results are rather mixed. There seems to bc a corrclation between the degree of independence of the central bank and the level of public debt. Furthermore weak evidence is found of the independence of the central bank influencing the rclation between the level of debt and inflation. No evidence is found, however, that independent central banks react more restrictive to rising structural deficits than dependent ones.
Keywords: C22; E58; 330; Geldpolitik; Zentralbankautonomie; Öffentliche Schulden; Haushaltsdefizit; Inflation; OECD-Staaten; Theorie